High production of 2,3-butanediol from biodiesel-derived crude glycerol by metabolically engineered Klebsiella oxytoca M1 - Cho, Sukhyeong; Kim, Taeyeon; Woo, Han Min; Kim, Yunje; Lee, Jinwon; Um, Youngsoon (BioMed Central, 2015)
Background: 2,3-Butanediol (2,3-BDO) is a promising bio-based chemical because of its wide industrial applications. Previous studies on microbial production of 2,3-BDO has focused on sugar fermentation. Alternatively, biodiesel-derived crude glycerol can be used as a cheap resource for 2,3-BDO production; however, a considerable formation of 1,3-propanediol (1,3-PDO) and low concentration, productivity, and yield of 2,3-BDO from glycerol fermentation are limitations. Results: Here, we report a high production of 2,3-BDO from crude glycerol using the engineered Klebsiella oxytoca M3 in which pduC (encoding glycerol dehydratase large subunit) and ldhA (encoding lactate dehydrogenase) were deleted to reduce the formation of 1,3-PDO and lactic acid. In fed-batch fermentation with the parent strain K. oxytoca M1, crude glycerol was more effective than pure glycerol as a carbon source in 2,3-BDO production (59.4 vs. 73.8 g/L) and by-product reduction (1,3-PDO, 8.9 vs. 3.7 g/L; lactic acid, 18.6 vs. 9.8 g/L). When the double mutant was used in fed-batch fermentation with pure glycerol, cell growth and glycerol consumption were significantly enhanced and 2,3-BDO production was 1.9-fold higher than that of the parent strain (59.4 vs. 115.0 g/L) with 6.9 g/L of 1,3-PDO and a small amount of lactic acid (0.7 g/L). Notably, when crude glycerol was supplied, the double mutant showed 1,3-PDO-free 2,3-BDO production with high concentration (131.5 g/L), productivity (0.84 g/L/h), and yield (0.44 g/g crude glycerol). This result is the highest 2,3-BDO production from glycerol fermentation to date. Conclusions: 2,3-BDO production from glycerol was dramatically enhanced by disruption of the pduC and ldhA genes in K. oxytoca M1 and 1,3-PDO-free 2,3-BDO production was achieved by using the double mutant and crude glycerol. 2,3-BDO production obtained in this study is comparable to 2,3-BDO production from sugar fermentation, demonstrating the feasibility of economic industrial 2,3-BDO production using crude glycerol.